Unpacking Poverty Determinant in Papua with Economic Growth as an Intervening Variable - Amelia, Nalendra Rizka; Susilo (Journal of Development Economic and Social Studies, 2025)
The implementation of the ‘No Poverty’ SDGs in Papua faces many challenges. In 2022, Papua recorded the highest percentage of poor people in Indonesia (26.8%), while recording the second highest GRDP growth nationally (14.8%). Although capital accumulation continues to increase, high economic growth has not been in line with poverty reduction. This study aims to analyze the effect of special autonomy funds, capital expenditure, investment, and population growth on economic growth and poverty in Papua with panel data of 29 districts/cities for the period 2017-2022 using SmartPLS 4. The results show that special autonomy funds increase economic growth and can reduce poverty through targeted labor-intensive programs. Capital expenditure have no significant effect on economic growth or poverty. Investment have no significant effect on economic growth and increase the poverty. Population growth has a negative impact on economic growth but reduces poverty through the informal sector. Economic growth itself has no effect on poverty because it is too dependent on the mining sector. In addition, there is no effect of economic growth as an intervening variable, indicating that the fiscal role in creating sustainable development in Papua has not been optimized. These findings can be used to determine policies for efficiency and targeting accuracy in allocating funds and the need for inclusive economic growth to reduce poverty in Papua.